2019
DOI: 10.1108/jamr-09-2018-0079
|View full text |Cite
|
Sign up to set email alerts
|

Arcs of communication and small- and medium-sized enterprise performance

Abstract: PurposeThe purpose of this paper is to analyse the information shared by SMEs with their main customers and suppliers and its implications on their performance.Design/methodology/approachThe paper puts forward the concept of arcs of communication based on the frequency and direction of the information exchanged by SMEs with their main customers and suppliers. SMEs are classified by the arc of communication they belong to using data from a survey carried out in the Canary Islands (Spain). The Rasch Measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Several previous studies found a direct positive impact between collaboration and business performance, such as Yanes-Estévez et al [43], which focused on the importance of effectively managing relationships between SMEs, the suppliers, and consumers. This was in line with the strategies to enhance cooperation in the supply chain, as successful company often consistently outperformed relevant competitors.…”
Section: The Relationship Between Collaboration and Innovation With B...mentioning
confidence: 98%
“…Several previous studies found a direct positive impact between collaboration and business performance, such as Yanes-Estévez et al [43], which focused on the importance of effectively managing relationships between SMEs, the suppliers, and consumers. This was in line with the strategies to enhance cooperation in the supply chain, as successful company often consistently outperformed relevant competitors.…”
Section: The Relationship Between Collaboration and Innovation With B...mentioning
confidence: 98%
“…For example, inter-organizational communication holds significant importance, particularly in the domains of sales and procurement (Wang et al, 2016;Butt, 2019). Various studies have explored specific aspects, such as the analysis of buyer-supplier personal ties (Christiansen et al, 2003;Saad et al, 2015;Agarwal & Narayana, 2020), as well as communication activities between buyers and suppliers (Li et al, 2023;Yanes-Estévez et al, 2019). While these research endeavors have sought to detail the communication patterns among employees of different companies, they have, however, overlooked the influence of personal ties outside the professional context in this specific context.…”
Section: Literature Review 21 Inter-organizational Communicationmentioning
confidence: 99%
“…In our survey, we further came across a variety of (corresponding) terms, ranging from "growth" [ 8 ] over "capacity" and "breadth" [ 19 ] to "scalability" [ 9 , 12 , 99 ] when referring to volume (e.g., used by [ 9 , 137 ]). Contrarily, velocity was discussed less prominently: Apart from the synonym "frequency" [ 206 ], we only attribute frequency-related aspects of scalability to this property. As an alternative for variety (e.g., used by [ 9 ]), we found the use of "heterogeneity" [ 175 ].…”
Section: An Information Flow Taxonomymentioning
confidence: 99%